Pengaruh sanksi perpajakan terhadap kepatuhan wajib pajak orang pribadi di Kantor Pelayanan Pajak Pratama Madiun - Faradilla Savitri Elva Nuraina (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study describes the effect of tax penalties to compliance of individual taxpayers in the Tax Office Primary Madiun. The method in this research is descriptive quantitative method while sampling technique in this research is incidental sampling technique that taxpayers in STO Madiun totaling 385 people. Collecting data using the method of observation, questionnaire, and documentation. In analyzing the data using simple linear regression analysis which includes validity, reliability, normality test, and to test the hypothesis proposed in this study using linear regression and t test. The results showed that the effect on the Taxation Penalties Taxpayer Compliance. It is obtained from the value t arithmetic amounted to 26.664 with a significance level of 0.000. Because 26.664> 1.966 and 0.000 <0.05 then Ho is rejected and Ha accepted.